Analisis Framing Pada Kasus Hukum Eks Gubernur Kalimantan Selatan Pada Media Massa Online Kompas.Com Dan Detik.Com - Redho Madani; Muzahid Akbar Hayat; Risma Ria; Suari Rosalia; Ahmad Ridhani (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the framing of legal news coverage concerning the former Governor of South Kalimantan, H. Sahbirin Noor, on Kompas.com and Detik.com during the period from October 6 to November 12, 2024. The case, which originated from a Corruption Eradication Commission (KPK) sting operation and the subsequent designation of Sahbirin Noor as a suspect in an alleged bribery case, ultimately concluded with the annulment of his suspect status through a pretrial court ruling. This research employs a qualitative method using Robert Entman’s framing model to examine how both media outlets frame the issue and shape public perception. Eight news articles were analyzed as the primary sample. The findings indicate significant differences in framing orientation between the two media platforms. Detik.com emphasizes a repressive–procedural approach, focusing on individual legal actions and demands for strict law enforcement. In contrast, Kompas.com adopts a preventive–systemic approach, viewing the case as part of broader governance issues and highlighting weaknesses in bureaucratic oversight. This study concludes that Detik.com places greater emphasis on the factual aspect of “what happened,” while Kompas.com highlights “why” and “how” the events occurred, thereby offering complementary constructions. These findings contribute to the study of political communication and digital journalism in understanding the relationship between media, power, and contemporary public opinion in modern Indonesia